Business Feasibility and Strategic Development of the Barokah Collection Fashion Store in Karangdadap, Pekalongan: A Qualitative Assessment - Fifiani Dwi Kurnia; M Taufiq Abadi (Econetica: Jurnal Sosial, Ekonomi, dan Bisnis, 2023)
This study investigates the business feasibility and strategic development of Barokah Collection, a small-scale fashion enterprise located in Karangdadap, Pekalongan, Indonesia. The research employs a qualitative descriptive method to assess key dimensions of feasibility, including economic, demographic, legal, human resource, operational, marketing, and financial aspects. Data were collected through in-depth interviews, observation, and documentation, and analyzed using Miles and Huberman’s interactive model. The findings reveal that Barokah Collection demonstrates strong feasibility and growth potential supported by favorable local economic conditions, compliance with legal frameworks, and a loyal customer base within the Islamic fashion market. However, limitations remain in digital marketing, financial system formalization, and workforce digital literacy. The study concludes that the long-term sustainability of microenterprises such as Barokah Collection depends on innovation, technological adoption, and strategic institutional collaboration. The results contribute to the literature on SME feasibility and entrepreneurship development in emerging markets.